Quo Vadis Employee Participation concerning Share Ownership in Companies in Indonesia - Sari, Andari Yuriko; Wicaksana, Arif; Amriyati, Amriyati; Utomo, Gabriel Bramantyo (Green Publisher Indonesia, 2023)
In general, in various companies, workers are rarely considered company assets, so that in various company developments, the role of workers is not an important thing to consider. However, along with the times, workers are then considered as company assets and have even begun to develop in various companies that include workers in share ownership of the company concerned and by participating in company share ownership (ESOP: Employee Stock Ownership Program), thus workers feel become part of the company. Article 43 Paragraph (3) letter a Law no. 40 of 2007 concerning Limited Liability Companies (“UUPT”) basically states that companies can offer shares to their own employees. However, basically there is no obligation for companies to include their workers in the ownership of company shares according to the Company Law. The problems in share ownership in companies for workers are (1) What are the legal problematic dilemmas regarding workers' participation in share ownership in companies in Indonesia? (2) What is the normative regulation of workers' share ownership in a company if it is to be regulated in sources of employment law, both autonomous and heteronomous? . In general, it can be concluded that there are still many obstacles in terms of workers wanting to be included in company ownership because according to laws and regulations participation in company share ownership is not a mandatory thing for companies to do, but must be an initiative of workers' associations and/or unions. Apart from that, there is also the problem of how to regulate normatively related to share ownership in the company for workers so that workers have a legal basis to own shares in the company.